The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1021/ic802278r
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium(II) Complex Formation with Cysteine and Penicillamine

Abstract: The complex formation between cadmium(II) and the ligands cysteine (H2Cys) or penicillamine (H2Pen = 3, 3′-dimethylcysteine) in aqueous solutions, containing CCd(II) ∼ 0.1 mol dm-3 and CH2L = 0.2 – 2 mol dm-3, was studied at pH = 7.5 and 11.0 by means of 113Cd-NMR and Cd K- and L3-edge X-ray absorption spectroscopy. For all cadmium(II)-cysteine mole ratios the mean Cd-S and Cd-(N/O) bond distances were found in the ranges 2.52 – 2.54 Å and 2.27 – 2.35 Å, respectively. The corresponding cadmium(II)-penicillamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
72
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(80 citation statements)
references
References 55 publications
8
72
0
Order By: Relevance
“…This result is remarkable because, in contrast to Cys and hCys, only a single SMW Cd complex eluted from the column. In order to rationalize this finding, previous studies revealed that in an aqueous solution at pH 7.0, the interaction of Cd with Cys results in the formation of the monomeric Cd species (possibly Cys 4 Cd) and the multimeric Cd species (possibly Cd 3 Cys 9 ) [52]. Since in the latter Cd complex Cd is coordinated to a thiol and a carboxylate group, blocking the carboxylate group with the ester moiety (Fig.…”
Section: Resultsmentioning
confidence: 86%
“…This result is remarkable because, in contrast to Cys and hCys, only a single SMW Cd complex eluted from the column. In order to rationalize this finding, previous studies revealed that in an aqueous solution at pH 7.0, the interaction of Cd with Cys results in the formation of the monomeric Cd species (possibly Cys 4 Cd) and the multimeric Cd species (possibly Cd 3 Cys 9 ) [52]. Since in the latter Cd complex Cd is coordinated to a thiol and a carboxylate group, blocking the carboxylate group with the ester moiety (Fig.…”
Section: Resultsmentioning
confidence: 86%
“…Based on these EXAFS data, the Cd species that eluted from the HPLC column is identified as the approximately tetrahedral (GS) 4 Cd. Even though the XAS data were acquired at 10 K, the formation of (GS) 4 Cd at room temperature has been recently reported [73] and it is therefore very likely that this species was also formed on the column.…”
Section: Structural Characterization Of the Gs X Cd Species That Elutmentioning
confidence: 99%
“…Particularly, D-penicillamine (Pen -Cuprimine, Depen), that has long been used as the drug of choice in the treatment of Wilson's disease or hepatolenticular degeneration, is a potential and effective chelator for some transition metals [12][13][14].…”
Section: Introductionmentioning
confidence: 99%